Study of the effect of changing the microstructure of titania layers on composite solar cell performance - Xie, Z; Henry, B; Kirov, K; Smith, H; Barkhouse, A; Grovenor, C; Assender, H; Briggs, G; Webster, G; Burn, P; Kano, M; Tsukahara, Y (2006)
This paper reports a study of the microstructures of titania thin films fabricated by two methods; doctor blade casting and glancing angle deposition (GLAD). The microstructures were characterised by a broad range of techniques, including SEM, HRTEM, and XRD. Porous films with a three-dimensional network of interconnected TiO2 particles were obtained using the doctor blade technique. GLAD was used to fabricate well-defined columnar structures. The power efficiency of composite solar cells (CSCs) based on doctor-bladed titanium dioxide and a spin coat MEH-PPV layer is reproducibly greater than 0.5% at 800 W/m(2), using a solar simulator and 420 rim UV blocking filter, with typical values J(sc) = 14.3 A/m(2), V-oc=0.79 V and FF=36%. This performance is significantly better than that reported for similar devices by other groups [1,2]. Under the same illumination conditions, preliminary results for CSCs based on GLAD titanium dioxide gave at best efficiencies of only 0.08%, with J(sc)=2.4 A/m(2), V-oc=0.61 V and FF=43%. We discuss how the morphology, crystal structure and optical absorption properties of the two types of TiO2 affect the overall device performance. (c) 2005 Elsevier B.V. All rights reserved.